BAHASA DAN SASTRA BALI DALAM KONTEKS BAHASA DAN SASTRA JAWA KUNA - I Made Suweta (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
Balinese is the mother tongue, which is the first language obtained from her mother or thelanguage used since birth to native Balinese. The connection of Old Javanese language withBalinese Language cannot be taken away in a cultural study that exists today. Various cases thatcan be found through the alkururat between Balinese residents and the spread of Javanesepeople who came to Bali. This can be attributed to a number of archipelago histories, includingthe sources of the collapse of the Majapahit kingdom and the culture brought to Bali, and can beattributed to the ancient Javanese language having a connection with Balinese. Based on aglimpse of the background, there are a number of problems that will be examined by formulatingthe following: (1) how is the distribution of Old Javanese language in Bali ?, (2) how is thevariety of Old Javanese languages absorbed by Balinese language ?, and (3) how the developmentof Old Javanese Language in the case of Balinese literature? Related to the study of Balineselanguage and literature in the context of Old Javanese language and literature, the followingcan be briefly presented as the results of the study as follows. (1) the spread of Old Javaneselanguage to Balinese language includes acculturation of culture brought about by the collapseof the Majapahit kingdom, so that all Old Javanese literary literature is brought to Bali, (2) thetype of absorption words used in Balinese include intralinguistic factors and extralinguisticfactors, (3) the development of Old Javanese in Balinese literature is an acculturation from OldJavanese to Balinese, and vice versa, which can be seen in literary works in the form of Gancaran,kakawin, and Palawakya.